2016
DOI: 10.1371/journal.pntd.0004616
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Typhoid and Paratyphoid in India: Systematic Review and Meta-analysis

Abstract: BackgroundTyphoid is an important public health challenge for India, especially with the spread of antimicrobial resistance. The decision about whether to introduce a public vaccination programme needs to be based on an understanding of disease burden and the age-groups and geographic areas at risk.MethodsWe searched Medline and Web of Science databases for studies reporting the incidence or prevalence of typhoid and paratyphoid fever confirmed by culture and/or serology, conducted in India and published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 28 publications
(37 reference statements)
6
125
3
3
Order By: Relevance
“…The incidence of S. typhi is estimated to be approximately 100 cases for 100 000 inhabitants per year in Southcentral and Southeast Asia 4 15. In a recent systematic review, the pooled estimate of typhoid burden in India was found to be 377 (178–801) per 100 000 person-years for typhoid 16. The incidence is significantly lower in the developed countries with a reported incidence of 0.31 cases per 100 000 in the year 2014 in the European Union countries, and predominantly acquired during travel to endemic countries particularly South Asia 17…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of S. typhi is estimated to be approximately 100 cases for 100 000 inhabitants per year in Southcentral and Southeast Asia 4 15. In a recent systematic review, the pooled estimate of typhoid burden in India was found to be 377 (178–801) per 100 000 person-years for typhoid 16. The incidence is significantly lower in the developed countries with a reported incidence of 0.31 cases per 100 000 in the year 2014 in the European Union countries, and predominantly acquired during travel to endemic countries particularly South Asia 17…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis suggested that the incidence of laboratory confirmed enteric fever is falling across India. However, the authors state that this is based on hospital studies from varying locations and thus is subject to confounding factors such as pre‐hospital use of antibiotics and variable health‐seeking behaviour .…”
Section: Epidemiology Of Enteric Fever In Indiamentioning
confidence: 99%
“…Although the worldwide fatality rate for typhoid fever has fallen to 1%, the annual global burden is 12 million cases (John et al . ). Children in urban areas on the Indian subcontinent are particularly affected.…”
Section: Introductionmentioning
confidence: 97%